Aspek Hukum Tata Negara Terhadap Pengangkatan dan Pemberhentian Hakim Mahkamah Konstitusi - Muhammad Azkannasabi; Dodi Jaya Wardana; Ifahda Pratama Hapsari (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research was motivated by the dismissal of Aswanto as a constitutional judge by the DPR, who legally and constitutionally still served as a constitutional judge. This research aims to find out aspects of constitutional law related to the appointment and dismissal of constitutional judges and to find out the implications of Constitutional Court Decision Number 96/PPU-XVIII/2020and the implications of Aswanto's dismissal as a constitutional judge. This research uses normative legal research. With a statutory approach, conceptual approach and case approach. The results of this research are that constitutional judges are proposed by the President, the House of Representatives and the Supreme Court with a mechanism regulated separately by the institution that nominates constitutional judges while not violating the provisions of the Law and in its implementation it must be open with the principles of transparency, participatory, objective and accountable. The implications of the Constitutional Court Decision Number 96/PPU-XVIII/2020 provide legal certainty regarding the tenure of incumbent constitutional judges and maintain the independence and impartiality of constitutional judges. The DPR's action to dismiss Aswanto constitutes a legal vacuum (rechstvacuum) because there are no regulations governing the DPR's authority to dismiss constitutional judges. The legal implications that occurred in the dismissal of Judge Aswanto by the DPR included legal uncertainty, inconsistency between the DPR and the President in implementing statutory regulations, problems with the independence of constitutional judges, and leading to the invalidity of the Presidential Decree.